2020
DOI: 10.3389/fphys.2020.00824
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Blood Pressure in Hypertensive Mice Fails to Fully Reverse Vascular Stiffness

Abstract: Background: Hypertension is a well-established driver of vascular remodeling and stiffening. The goal of this study was to evaluate whether restoring normal blood pressure (BP) fully restores vascular stiffness toward that of normotensive controls. Methods: C57Bl6/J male mice received angiotensin II (angII; 1 µg/kg/min) via infusion pump for 8 weeks (hypertension group: HH), angII for 4 weeks (hypertension group: H4), angII for 4 weeks followed by 4 weeks of recovery (reversal group: HN), or sham treatment (no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
(73 reference statements)
1
12
0
Order By: Relevance
“…While there are several classes of therapeutic agents to control pressure ( Chobanian, 2017 ; Cuspidi et al, 2018 ; Unger et al, 2020 ), ACE inhibitors are highly recommended because of their cardio- and vascular protective effects ( Ferrari et al, 2005 ; Janic et al, 2014 ; Chobanian, 2017 ). This study confirmed the participation of RAS in hypertension, as shown elsewhere ( Marque et al, 2002 ; Safar, 2010 ; Hong et al, 2013 ; Natalin et al, 2016 ; Mancini et al, 2017 ; Steppan et al, 2020 ), since 8 weeks of perindopril treatment significantly reduced BP (−11%), as shown by the time course of SBP. We did not measure PWV at the beginning of the treatment, but since we have shown that PWV positively correlates with BP in SHR ( Fabricio et al, 2020 ), we may assume that PWV was also high at the beginning of the protocol.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…While there are several classes of therapeutic agents to control pressure ( Chobanian, 2017 ; Cuspidi et al, 2018 ; Unger et al, 2020 ), ACE inhibitors are highly recommended because of their cardio- and vascular protective effects ( Ferrari et al, 2005 ; Janic et al, 2014 ; Chobanian, 2017 ). This study confirmed the participation of RAS in hypertension, as shown elsewhere ( Marque et al, 2002 ; Safar, 2010 ; Hong et al, 2013 ; Natalin et al, 2016 ; Mancini et al, 2017 ; Steppan et al, 2020 ), since 8 weeks of perindopril treatment significantly reduced BP (−11%), as shown by the time course of SBP. We did not measure PWV at the beginning of the treatment, but since we have shown that PWV positively correlates with BP in SHR ( Fabricio et al, 2020 ), we may assume that PWV was also high at the beginning of the protocol.…”
Section: Discussionsupporting
confidence: 90%
“…Even though it is not clear whether arterial stiffness precedes hypertension or it is a consequence ( Kaess et al, 2012 ; Mitchell, 2014 ; Celik et al, 2017 ; Rode et al, 2020 ), several studies have shown a significant correlation between PWV and BP ( Laurent et al, 2009 ; Phillips et al, 2015 ; Steppan et al, 2020 ), including the present study, and the growing incidence of cardiovascular events in patients with high PWV values is eminent ( Niiranen et al, 2017 ; Nilsson Wadstrom et al, 2019 ; Scuteri et al, 2020 ). Therefore, it is important to determine the mechanisms involved in vascular stiffening.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations